Purulent Cellulitis In A 50-Year-Old Patient With A History Of Hypertension - Devin Alexander; Muhammad Rivandio A. S. (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Cellulitis is an acute diffuse bacterial infection involving the dermis and subcutaneous tissue. It may be classified as purulent or non-purulent cellulitis. Lower-extremity involvement is common, and comorbid vascular disease or impaired circulation may increase the risk of infection. Case Description: A 50-year-old woman presented to the emergency department with left leg pain, fever, swelling, erythema, and purulent ulcers. She had a history of hypertension and was not taking medication regularly. Physical examination revealed blood pressure of 181/86 mmHg, left crural ulcers with slough and necrotic tissue, and pitting edema. Laboratory examination showed leukocytosis, while chest radiography showed cardiomegaly with aortic calcification. The patient was diagnosed with suspected peripheral arterial disease accompanied by purulent cellulitis. She received intravenous antibiotics, analgesics, supportive therapy, wound care, and incision of bullae during hospitalization, with clinical improvement. Conclusions: Purulent cellulitis requires prompt recognition and treatment. Ulcers may serve as a portal of entry for skin flora, while hypertension and vascular compromise may contribute to impaired tissue perfusion and edema. Antibiotic therapy, drainage when indicated, wound care, and bacterial culture for definitive therapy are important components of management.